1975
DOI: 10.1037/h0076766
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on Bem's measurement of psychological androgyny: Alternative methods and a supplementary analysis.

Abstract: The drawbacks of a t ratio measure of psychological androgyny are discussed. Other measurement approaches are indicated, and a substantive issue is addressed. Bern (1974) recently described a sex-role inventory that provides separate Femininity and Masculinity scale scores and uses their f-ratio difference as a measure of psychological androgyny. There are, however, both descriptive and inferential problems associated with the application of Student's t. This article describes these problems, suggests their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1979
1979
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 2 publications
(1 reference statement)
1
38
0
1
Order By: Relevance
“…If femininity and masculinity scores were approximately equal, then that person was deflned as 'androgynous'. However, this scoring method was subject to an influential critique by Spence, Helmreich and Stapp (1975) and Staham (1975) who claimed that such a deflnition of androgyny obscured the distinction between individuals who score high on femininity and high on masculinity, and those who score low on both. Bem endorsed their recommendation that a 'median split method' be used on the basis that high-high ('androgynous') and low-low ('undifferentiated') individuals did appear to comprise distinct groups.…”
Section: Variabte Measurement A) Gender and Sexmentioning
confidence: 99%
“…If femininity and masculinity scores were approximately equal, then that person was deflned as 'androgynous'. However, this scoring method was subject to an influential critique by Spence, Helmreich and Stapp (1975) and Staham (1975) who claimed that such a deflnition of androgyny obscured the distinction between individuals who score high on femininity and high on masculinity, and those who score low on both. Bem endorsed their recommendation that a 'median split method' be used on the basis that high-high ('androgynous') and low-low ('undifferentiated') individuals did appear to comprise distinct groups.…”
Section: Variabte Measurement A) Gender and Sexmentioning
confidence: 99%
“…This approximate method is preferred because, unlike the actual ! score, it does not confound mean level difference with variability of ratings (Strahan, 1975). Yet, the 120.…”
mentioning
confidence: 99%
“…Several researchers (e.g., Bem, 1977;Strahan, 1975) have advocated multiple regression techniques to examine separate and combined effects of masculinity and femininity on dependent variables of interest. Multiple regression may well be the method of choice for identifying combinations of masculinity and femininity traits that account for the most variance in particular criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting score, called a t-ratio, is similar in principle to the familiar Student's t statistic. Strahan (1975) criticized this procedure on the grounds that it violated statistical assumptions underlying Student's t. He suggested that the simple unadjusted difference score (F-M) estimated the t-ratio quite accurately and could be used instead. Spence et al (1975) described a different scoring procedure.…”
Section: Previous Scoring Proceduresmentioning
confidence: 98%